THE SPECIFICS OF THE VALUE RESEARCH METHODOLOGY IN THE INNOVATION ECONOMY - D. Zukhba (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the article there were identified peculiarities of the analysis methodology of innovation’s value, which are adequate to the current state of the economic system and the level of development of science. There were proved that the peculiarities of the methodology are related with the use of evolutionary approach, taking into account the bifurcation process, synergies, depending on the path of development.